(untitled) (International Journal of Physiotherapy, 2016)
Background: Children were major part of our society and their health issues were too much, so it’s necessary that child should b healthy so their health assessment is important worldwide the acceptable method for assessment of health status is anthropometry (weight & height). This study was done to assess the anthropometric measurement of primary school going children of Karachi, sindh Pakistan, and evaluate how much students were underweight. Methods: The study was done in different primary school of Karachi including private semiprivate and government. The study design was cross sectional study. The sample size of our study was 240, including both genders male& female with range between 7-12 years. Result: The result shows that 34.9% were underweight (below 5th percentile), 63.44% were normal weight (between 5-95th percentile) and only0.8% overweight (above 95th percentile).The result showed male-female ratio was 51.5% boys and 48.5% were underweight. The prevalence of underweight in private sector was only 9.5% but in government it was 45.5%.The height of student also calculated and 26.3% children were below the 5th percentile of height for the age, 62.8% were between 5th to 95th percentile and 10.9% above 95thpercentile. Conclusion: The prevalence of underweight in primary school going children in Karachi shows the dietary requirements of children are not fulfilled properly and this may lead to many sever pathological conditions, so it is necessary to take positive steps regarding awareness of proper diet, hygiene and growth & development of child.